Syncrip regulates mRNA localisation and translation at the drosophila neuromuscular junction - Halstead, J (2013)
Evidence in different systems suggests that local translation is involved in synaptic plasticity in both neuron and muscle, but the mechanism by which this occurs is still poorly understood. The mRNA-binding protein Syncrip is conserved from fly to mammals and is thought to be involved in localized translation in both oocytes and neurons. Previous work has shown that Syncrip associates with mRNAs encoding key synaptic proteins at the Drosophila larval neuromuscular junction. Here I show that Syncrip is necessary for the structure and function of the neuromuscular junction. First, the loss of Syncrip leads to overgrowth of the neuromuscular junction. Second, Syncrip is required for proper expression of the Ca2+-sensor Synaptotagmin1 at the presynapse, and loss of Syncrip causes a decrease in vesicle release probability. Third, while it was not possible to measure mRNA distribution in neurons, Syncrip mutants, like other perturbations in synaptic plasticity, correlate with changes in mRNA localization in muscle. Fourth, the overexpression and loss of Syncrip function suggest that the nuclear and nucleolar trafficking of the eukaryotic translation initiation factor eIF4E may be important to regulating synaptic morphology. These data suggest that Syncrip is involved in mRNA localization and translation in synaptic plasticity.